2014
DOI: 10.1890/13-0757.1
|View full text |Cite
|
Sign up to set email alerts
|

Trait–environment relationships remain strong despite 50 years of trait compositional change in temperate forests

Abstract: Temperate North American forest communities have changed considerably in response to logging, fragmentation, herbivory, and other global change factors. Significant changes in the structure and composition of seemingly undisturbed Wisconsin forest communities have occurred over the past 50 years, including widespread declines in alpha and beta species diversity. To investigate how shifts in species composition have affected distributions of plant functional traits, we first compiled extensive data on understor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 83 publications
6
52
2
Order By: Relevance
“…However, at all spatial scales (10 × 10 m, 20 × 20 m, and 50 × 50 m), perhaps unexpectedly, we found that species with a large seed mass preferred the resource-rich part of the plot, while small-seeded species were distributed in the nutrient-limited part of the plot. A similar report also showed that large seed mass associated with nutrient-rich environments 41 . In summary, variation in the soil resource availability at these scales shapes the distribution of functional traits in a tropical forest.…”
Section: Discussionmentioning
confidence: 61%
“…However, at all spatial scales (10 × 10 m, 20 × 20 m, and 50 × 50 m), perhaps unexpectedly, we found that species with a large seed mass preferred the resource-rich part of the plot, while small-seeded species were distributed in the nutrient-limited part of the plot. A similar report also showed that large seed mass associated with nutrient-rich environments 41 . In summary, variation in the soil resource availability at these scales shapes the distribution of functional traits in a tropical forest.…”
Section: Discussionmentioning
confidence: 61%
“…We determined the dispersal mode of our 26 most common quadrat species by referring to a plant traits database compiled from literature and field specimens (Amatangelo et al . ). The sapling (0·6 cm ≤ DBH <10 cm) and tree tallies were converted to plot‐level averages for hardwood and conifer sapling and overstory basal area (BA, m 2 ha −1 ).…”
Section: Methodsmentioning
confidence: 97%
“…Life history traits and range characteristics served to predict extinction risk due to climate change in some regions (Pearson et al ., ), but these responses are complex and rarely generalize to predict range shifts across a broad range of taxa (Angert et al ., ). In studies resurveying multiple species across many sites, species’ traits can help to disentangle diverse drivers of ecological change (Leach & Givnish, ; Damschen et al ., ; Crimmins et al ., ; Soudzilovskaia et al ., ; Amatangelo et al ., ; Savage & Vellend, ). It is thus reasonable to suppose that traits might help explain the complex responses of individual species to climate change.…”
Section: Introductionmentioning
confidence: 99%